ANTIOXIDANT ACTIVITY OF METHANOL EXTRACT NATUNA MARINE SPONGE (PORIFERA) WITH DPPH METHODE - MAYEFIS, DELLADARI; WIDIASTUTI, SISKA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Natuna sponge is a marine animal that contains a wide range of secondary metabolites that can be utilized in the field of pharmacy. The research aims to test the phytochemical content and antioxidant activity of the Natuna methanol marine sponge extract. Sample extraction is done by the maceration method with methanol solvent. Methods: Phytochemical tests include alkaloid testing, flavonoids, steroids, saponins, and tannins. Test antioxidant activity using the immersion DPPH method (1.1-diphenyl-2-picryl hydroxyl) measured absorption at a wavelength of 517 nm. Results: The phytochemical test results showing the sponge of Natuna contain secondary metabolites including alkaloids, flavonoids, steroids, saponins, and tannins. Conclusion: This Natuna sponge methanol extract has an antioxidant activity that is very strong with an IC50 value of 52.91 ppm, and the comparator used is Vitamin C with an IC50 value of 43,51 ppm.